Type of whelping and its infleunce on Apgar score - N, Arunmozhi; A. Subramani; P. Sridevi; M. Shafiuzama; Cecilia Joseph; K. Krishnakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The modified Apgar score for puppies was evolved based on the reference range of heart rate, respiration, irritability reflex, motility and membrane mucous colour according to the physiology of canine neonate. A total of 100 puppies born to the bitches that underwent Spontaneous Whelping (SW), Assisted Whelping (AW) and Caesarean section (CS) were selected and were divided into III groups viz. SW (n=30), AW (n=35) and CS (n=35).A modified Apgar score model was used to assess neonatal viability of the puppies. Among the total 100 pups evaluated 36, 13 and 51 pups were having Apgar scores of 0 to 4, 5 to 9 and 10 to 14, respectively. Out of 36 pups having Apgar scores of 0 to 4 at birth, 5.56, 19.44 and 75.00 per cent of pups were born through SW, AW and CS, respectively. Among 13 pups born with Apgar scores of 5 to 9 at birth, 0, 38.46 and 61.54 per cent of pups were born through SW, AW and CS, respectively. Out of 51 pups with Apgar scores of 10 to 14 at birth, 54.90, 45.10 and 0 per cent of pups were born through SW, AW and CS, respectively. Among the viable pups at birth, the pups born through CS were having low and medium Apgar scores of 0 to 4 and 5 to 9, respectively. All the pups delivered through SW had highest Apgar scores at birth while the pups delivered through AW had shown Apgar scores between 5 to 9 and 10 to 14.